2015
DOI: 10.17017/jfish.v3i3.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Fish fauna of the Brahmaputra River, Bangladesh: richness, threats and conservation needs

Abstract: The Brahmaputra River is one of the largest rivers in the world as well as in Bangladesh. The present study was carried out for a period of one year from January to December 2013 with a view to assessing the availability of fishes in the river with species emphasis on species richness, existing threats and conservation issues. Daytime and night sampling were carried out in three sites located along the upstream to downstream course of the river on a monthly basis. Three fishing gears including cast net, seine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 6 publications
13
33
1
Order By: Relevance
“…Results obtained through studies undertaken by several researchers have revealed same scenario (Galib et al 2009aSamad et al 2010;Chaki et al 2014;Mohsin et al 2013Mohsin et al , 2014Galib 2015;Joadder et al 2015).…”
Section: Catch Analysismentioning
confidence: 68%
“…Results obtained through studies undertaken by several researchers have revealed same scenario (Galib et al 2009aSamad et al 2010;Chaki et al 2014;Mohsin et al 2013Mohsin et al , 2014Galib 2015;Joadder et al 2015).…”
Section: Catch Analysismentioning
confidence: 68%
“…The number of recorded fish species from Kumari Beel was similar to various beels (MACH 2006;Mustafa et al 2014) and slightly lower than the Chalan Beel (Galib et al 2009a), Dahia Beel (Flowra et al 2009), Halti Beel (Imteazzaman and Galib 2013), Brahmaputra River (Galib 2015) and Mahananda River (Galib et al 2016). Most of the respondent (82%) mentioned that the fish species was decreasing day by day before establishing the fish sanctuary.…”
Section: Status and Catch Composition Of Fish Faunamentioning
confidence: 74%
“…Critically Endangered, Endangered and Vulnerable. Decreasing trend of freshwater fishes in various rivers of Bangladesh has already been reported by several researchers (Galib 2015;Joadder et al 2015;Chaki et al 2014;Mohsin et al 2014Mohsin et al , 2013Galib et al 2013). In a recent research Hossain (2014a) declared that 30 riverine fish species have became extinct though the researcher did not mention the methodology followed for his findings.…”
Section: Introductionmentioning
confidence: 94%